Perceived usefulness of mirrored video self-modeling in the development of bilateral competence in elite team-sports - Petro, B.; Ehmann, B.; Bárdos, G.; Szabo, A. (Journal of Human Sport & Exercise, 2018)
The use of video technology in perfecting athletic training has many benefits on performance. The aim of this study was to determine: (1) athletes' perception of the importance of bilateral skills in sports; (2) the prevalence of use of video feedback in individual skill development; and (3) athletes' attitude toward "mirrored" video self-modelling in four sports. A total of 20 elite athletes, from four popular team sports, were interviewed regarding the three issues using semi-structured interviews. The qualitative results indicate that bilateral skills are differently appreciated in the four team sports. They are perceived as the most important by soccer players, followed by basketball- and handball players and least important by the water polo players. These findings are in full synchrony with athletes` attitudes toward using mirrored video self-modelling. It emerges that the use of technology for developing bilateral skills, with the aim to improve sport performance, is currently sport specific and matches the actual worldwide ranking of the sports' popularity.